The Effect of Vlog Media with ARIAS Model (Assurance, Relevance, Interest, Assessment, and Satisfaction) Towards Students’ Verbal Communication Skills in Social Studies Learning - Nurdianty, Siska (Universitas Pendidikan Indonesia (UPI), 2021)
One of the dimensions of social studies learning is the skill, which includes communication skills. This study focuses on verbal communication through written and oral messages. This study aims at testing and observing the effectiveness of the vlog media with the ARIAS model on students' verbal communication skills at SMP Muhammadiyah 6 Bandung. Pre-experimental method used as the research method with the-one group pretest-posttest design. The sample of this research is students of class VIII-A at SMP Muhammadiyah 6 Bandung. The sole instrument used in this study is a test. After the data has been collected, it is processed using the hypothesis test or t-test using the SPSS v20 application. The results of the analysis showed that there was a change in students' verbal communication skills before and after using the vlog media treatment with the ARIAS model. The difference in students' verbal communication skills based on hypothesis testing, the significant value (sig 2-tailed) is 0.000 0.05, therefore H1 is accepted or H0 is rejected and the hypothesis is accepted. Thus, it can be concluded that the vlog media with the ARIAS model in social studies learning is effective for improving verbal communication skills for class VIII- A students of SMP Muhammadiyah 6 Bandung.Keyword: Vlog media; Verbal communication; Social studies learning